PELATIHAN DAN PENDAMPINGAN PENGGUNAAN APLIKASI MANAGEMENT STOCK CONTROL PADA UMKM PETERNAKAN LELE “RIZKY” KAMPUNG LELE BOYOLALI - Asih Handayani; Jemmy Bernardy; Dasmadi Dasmadi (Jurnal Abdimas Bina Bangsa, 2022)
The catfish village is a center for catfish farming in Boyolali Regency. Most of the people depend on the family economy from this sector. There are those who work as catfish breeders, consumption catfish breeders, feed sellers, catfish buyers, some are unskilled laborers in the farm. The IbM program is in collaboration with "RIZKY" Catfish Farming UKM partners managed by Mr. Irnawan and his wife Mrs. Dewi Rusmini, located in "Kampung Lele" Boyolali to be precise in the village of Mangkubumen Tegal Rejo, Sawit Boyolali with a distance of about 25 km from Slamet Riyadi University Surakarta . Mr. Irnawan and Mrs. Dewi in particular separated their business into two sectors, namely (1) as catfish breeders as well as catfish traders who, apart from selling their own crops, also bought other farmers' crops for sale by catfish traders, and (2) as feed traders, where they as a feed agent for their own consumption on their farms as well as being sold to other farmers affiliated with them. Community service this time is more focused on feed supply management which is managed by Mrs. Dewi. Community service activities focus on managing and applying management and inventory control including training in applying the Management Stock Control application to determine reorder levels and minimum stock